Light extraction efficiency enhancement of colloidal quantum dot light-emitting diodes using large-scale nanopillar arrays - Mutlugun, Evren (2014)
A colloidal quantum dot light-emitting diode (QLED) is reported with substantially enhanced light extraction efficiency by applying a layer of large-scale, low-cost, periodic nanopillar arrays. Zinc oxide nanopillars are grown on the glass surface of the substrate using a simple, efficient method of non-wetting templates. With the layer of ZnO nanopillar array as an optical outcoupling medium, a record high current efficiency (CE) of 26.6 cd/A is achieved for QLEDs. Consequently, the corresponding external quantum efficiency (EQE) of 9.34% reaches the highest EQE value for green-emitting QLEDs. Also, the underlying physical mechanisms enabling the enhanced light-extraction are investigated, which leads to an excellent agreement of the numerical results based on the mode theory with the experimental measurements. This study is the first account for QLEDs offering detailed insight into the light extraction efficiency enhancement of QLED devices. The method demonstrated here is intended to be useful not only for opening up a ubiquitous strategy for designing high-performance QLEDs but also with respect to fundamental research on the light extraction in QLEDs.